GROWTH AND YIELD OF EGGPLANT (Solanum melongena L.) ON VARIOUS COMBINATIONS OF N-SOURCE AND NUMBER OF MAIN BRANCH - Maghfoer, Mochmammad Dawam; Soelistyono, Roedy; Herlina, Ninuk (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2014)
This research was conducted to increase production of eggplants through combination of N-source and number of main branch has done onthe field of andosol in Poncokusumo - Malang, 600 m asl, pH 5.4, from August to December 2013. The experiment used a Randomized Complete Block Design with 2 factors and 3 replications. Factor 1 was proportion of inorganic - organic N fertilizer (138 kg N ha-1): 100% Urea, 75% Urea + 25% goat manure, 50% Urea + 50% goat manure, and 25% Urea + 75% goat manure. Factor 2 was number of main branches: 1, 2 and 3 main branches. Results showed that there was no interaction effect between treatment combinations of organic-inorganic sources of N and the number of main branches to all observed variables. Treatment using the combination of 75% Urea + 25% goat manure increased the plant growth and gave the highest fruit yield (49.20 t ha-1) in comparison with combination using other fertilizers and 100% Urea. The lowest was derived from the application of 100% Urea, 35.61 t ha-1. Cultivation of eggplant with 3 main branches has resulted better growth and fruit yield than 1 and 2 main branches, 50.85, 47.91 and 30.79 t ha-1, respectively.Keywords: eggplant, goat manure, main branch, urea